Otimização de multidões em jogos digitais utilizando CUDA - Bardella, Tiago Ungaro (2015)
The history of digital games shows, since the beginning, games which uses many types of enemy models to confront and many types of characters to control, like Real-Time Strategy games, for example. These huge amount of models into an important scene are called crowds. The crowds needs a high computer performance and specific algorithms in their interaction control to avoid immersion loss into a game by problems which may happen if the crowds are not treated accordingly. With the popularization of graphic board languages like NVIDIA CUDA, new algorithms were created to easily increase the performance of crowds in digital games and their overwhelming superiority compared to the methods used in linear programming were proved in many researches. The goal of this work is to use these GPU techniques as base to implement a new API using CUDA language that will present better performance and simplicity compared to the others algorithms on the area of crowds in digital games. After the project conclusion, the created API turned easier the crowd treatment to digital game developers using Unity3D integrated with API TBX, that now only need to include a DLL in the project instead creating na algorithm for crowd treatment from the beginning, which takes a huge amount of time from development.